2020
DOI: 10.3390/diagnostics10110883
|View full text |Cite
|
Sign up to set email alerts
|

Obesity in Qatar: A Case-Control Study on the Identification of Associated Risk Factors

Abstract: Obesity is an emerging public health problem in the Western world as well as in the Gulf region. Qatar, a tiny wealthy county, is among the top-ranked obese countries with a high obesity rate among its population. Compared to Qatar’s severity of this health crisis, only a limited number of studies focused on the systematic identification of potential risk factors using multimodal datasets. This study aims to develop machine learning (ML) models to distinguish healthy from obese individuals and reveal potential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 50 publications
1
7
0
Order By: Relevance
“…1 E): hiPSC-platelets were anucleate and possessed organelles seen in adult human blood donor platelets, including mitochondria, OCSs (open canalicular systems), and granules. We then performed light transmission aggregometry (LTA), a method used clinically to evaluate platelet function in vitro 67 69 , on hiPSC-platelets generated in vitro from hiPSCs and showed that 3 × 10 7 resting hiPSC-platelets resuspended in human plasma reached 50–60% aggregation at all time points analyzed after exposure to 20 µM ADP and TRAP (Fig. 1 F).…”
Section: Resultsmentioning
confidence: 99%
“…1 E): hiPSC-platelets were anucleate and possessed organelles seen in adult human blood donor platelets, including mitochondria, OCSs (open canalicular systems), and granules. We then performed light transmission aggregometry (LTA), a method used clinically to evaluate platelet function in vitro 67 69 , on hiPSC-platelets generated in vitro from hiPSCs and showed that 3 × 10 7 resting hiPSC-platelets resuspended in human plasma reached 50–60% aggregation at all time points analyzed after exposure to 20 µM ADP and TRAP (Fig. 1 F).…”
Section: Resultsmentioning
confidence: 99%
“…A further study conducted in Qatar confirmed that obesity risk factors (c-peptide, insulin, albumin, and uric acid) and obesity-related comorbidities such as diabetes (e.g., HbA1c, glucose), liver function (e.g., alkaline phosphatase, gamma-glutamyl transferase), lipid profile (e.g., triglyceride, LDL-c, HDL-c), as well as most of the dual-energy x-ray absorptiometry measurements (e.g., bone area, bone mineral composition, bone mineral density, etc.) were significantly ( p <0.05) higher in the obese group ( 129 ).…”
Section: Resultsmentioning
confidence: 84%
“…The Qatari population shows high rates of obesity in addition to other cardiovascular risk factors such as cigarette smoking, physical inactivity, diabetes, hypertension, and unhealthy diet patterns [26][27][28][29] . Furthermore, higher BMI and obesity is associated with the onset and development of several cancers including breast, lung, bladder, colorectal and prostate 30 ; these cancers are prominent in several Middle-Eastern countries including Qatar 31 .…”
Section: Discussionmentioning
confidence: 99%